Spatial variation patterns of vegetation and soil physicochemical properties of a typical inland riverscape on the Mongolian plateau - Ma, Linqian; Fu, Ruiying; Liu, Huamin; Zhang, Rui; Xu, Zhichao; Cao, Xiaoai; Liu, Xuhua; Wen, Lu; Zhuo, Yi; Wang, Lixin (Frontiers in Environmental Science, 2023)
The spatial distribution and heterogeneity of soil and vegetation, as the root of the maintenance of ecosystem services in the riparian zone, play a decisive role in the ecological functions of the riverscape. In this study, a field survey of wetland plant communities and soil sampling were conducted in both longitudinal and lateral dimensions from the perspective of the riverscape of the Ulgai River, a typical inland river on the Mongolian Plateau. The diversity of wetland plant communities, soil physicochemical properties, and the correlations between them were systematically analyzed. The results showed that a total of 87 species belonging to 65 genera and 24 families of plants were present, with Asteraceae, Poaceae, and Cyperaceae as the main families. The plant composition and species diversity in the riparian zone at different dimensions showed obvious spatial patterns of succession. Although the correlation coefficient and significance of the physicochemical properties of river length and river width in the study area were different, most correlations remained consistent, among which soil moisture, soil pH, and total carbon were correlated with many physicochemical factors. The soil ammonium and nitrate nitrogen along the river length direction and electrical conductivity and organic carbon content along the river width direction were the main limiting factors affecting the diversity and distribution of plant species in the riparian zone based on the redundancy analysis. This study provides a theoretical basis for the continuous improvement of the current soil quality and the restoration of the degraded wetland ecosystems of inland rivers in arid and semi-arid regions, as well as a new perspective for the study of riverscape ecology.